2007
DOI: 10.1038/sj.embor.7400932
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional bypass of bulky DNA lesions causes new mutant RNA transcripts in human cells

Abstract: Here, we characterize the mutant transcripts resulting from bypass of an 8,5 0 -cyclo-2 0 -deoxyadenosine (cyclo-dA) or cyclobutane pyrimidine dimer (CPD) by human RNA polymerase II (Pol II) in vivo. With the cyclo-dA lesion, we observed two new types of mutant transcripts. In the first type, the polymerase inserted uridine opposite the lesion and then misincorporated adenosine opposite the template deoxyadenosine downstream (5 0 ) of the lesion. The second type contained deletions of 7, 13 or 21 nucleotides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 25 publications
4
82
1
1
Order By: Relevance
“…However, this is probably a rare event as the presence of a CPD in the active site of RNAPII has been shown to strongly disfavor forward translocation of RNAPII ). Under certain conditions and likely with low frequency, bypass of helix distorting lesions such as CPDs and cyclo-dA may occur in yeast (Walmacq et al 2012) and in NER deficient human cells (Marietta and Brooks 2007). Yeast RNAPII was shown to bypass CPDs via an intrinsic ability to perform errorfree translesion synthesis, whereas bypass of bulky lesions in human XP-A cells resulted not only in transcription mutagenesis but also in nonmutant transcripts.…”
Section: Transcriptional Arrest and Its Coupling To Dna Damage Responmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is probably a rare event as the presence of a CPD in the active site of RNAPII has been shown to strongly disfavor forward translocation of RNAPII ). Under certain conditions and likely with low frequency, bypass of helix distorting lesions such as CPDs and cyclo-dA may occur in yeast (Walmacq et al 2012) and in NER deficient human cells (Marietta and Brooks 2007). Yeast RNAPII was shown to bypass CPDs via an intrinsic ability to perform errorfree translesion synthesis, whereas bypass of bulky lesions in human XP-A cells resulted not only in transcription mutagenesis but also in nonmutant transcripts.…”
Section: Transcriptional Arrest and Its Coupling To Dna Damage Responmentioning
confidence: 99%
“…Stalled transcription forms an acute problem for cellular homeostasis by depriving cells of vital messages. In addition, DNA lesions in the transcribed strand may induce mutant transcripts as a consequence of transcriptional bypass over DNA lesions (Doetsch 2002;Marietta and Brooks 2007). A sophisticated subpathway of NER has been evolved to specifically resolve transcription complexes stalled at DNA lesions, thus allowing restoration of transcription and successful production of essential transcripts.…”
Section: Nucleotide Excision Repair and Its Coupling To Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sessile organisms, plants are inevitably affected by UV radiation and other environmental stresses. UV light can penetrate cells and cause DNA damage; in particular cyclobutane pyrimidine dimers (CPDs) and pyrimidine (6-4) pyrimidone photoproducts [(6-4)PPs], that blocks or renders inaccurate replication and transcription; and leads to the mutagenic consequences [2]. For surviving, plants have evolved a number of adaptive strategies to overcome the stresses; such as physiological adaptation like biosynthesis of UV-absorbing compounds [3]; photoreactivation [1]; nucleotide excision repair (NER) [4] and translesion synthesis (TLS) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The small number of in vivo studies conducted to date have relied on luciferase reporter assays in bacterial cells to gauge TM caused by uracil or 8OG (13,14). Interestingly, a recent study of transcriptional encounters with 8,5Ј-cyclo-2Ј-deoxyadenosine and cyclobutane pyrimidine dimers in mammalian cells indicated that even bulky lesions that normally pose a significant block to transcription can be occasionally bypassed with mutagenic effects (15).…”
mentioning
confidence: 99%